Lithium ion battery with silicon-carbon negative electrode

By using silicon-carbon composite materials in the negative electrode sheet of the lithium-ion battery and introducing specific additives A1 into the electrolyte, a stable SEI film is formed, which solves the problem of poor circulation stability of the lithium-ion battery and improves the circulation performance and safety of the battery.

CN119518067APending Publication Date: 2025-02-25ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411715347.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the lithium-ion battery with silicon-carbon composite materials as the negative electrode has poor circulation stability, resulting in volume expansion of the battery during charging and discharging, and poor circulation stability.

Method used

By providing a negative electrode active material layer of silicon-carbon composite material in the negative electrode sheet of the lithium-ion battery, and introducing a specific additive A1 into the electrolyte solution, a compound having a structure of Formula I is formed to form a stable solid electrolyte membrane (SEI membrane) to improve the cycle stability of the battery.

Benefits of technology

By forming a stable SEI film, excessive decomposition of electrolyte components during battery circulation is avoided, the circulation performance and safety of the battery is improved, and the battery impedance is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518067A_ABST
    Figure CN119518067A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery with a silicon-carbon negative electrode, belongs to the technical field of lithium ion batteries, and overcomes the defect of poor cycling stability of a lithium ion battery with a silicon-carbon composite material as a negative electrode in the prior art. According to the lithium ion battery with the silicon-carbon negative electrode, a negative electrode active material layer comprises a silicon-carbon composite material; the Raman spectrum characteristics of the silicon-carbon composite material meet the following conditions: (D1 + D3) / (D2 + D4) = K, wherein K is more than or equal to 0.5 and less than or equal to 3; d1, D2, D3 and D4 correspond to the intensities of the characteristic peak 1, the characteristic peak 2, the characteristic peak 3 and the characteristic peak 4 respectively; and the electrolyte comprises an additive A1. And the additive A1 interacts with the specific silicon-carbon material, so that the generation of an SEI film is promoted, and the ionic conductivity, the stability and the elasticity of the SEI film are improved, thereby improving the cycling stability and the safety of the silicon-carbon battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery with a silicon-carbon negative electrode. Background Art

[0002] Currently, lithium-ion batteries are widely used in portable digital products, electric vehicles, energy storage devices, etc. due to their excellent electrochemical performance, physical properties and reliable safety performance. These advantages enable lithium-ion batteries to meet the needs of modern society for efficient, lightweight and sustainable energy solutions, thus becoming the preferred energy storage device for various application scenarios. With the growing demand for energy storage devices, how to further improve the energy density of batteries has become a key task for R&D personnel.

[0003] The theoretical specific capacity of silicon-carbon composite materials is much higher than that of traditional graphite negative electrode materials. Silicon materials can reach 4200mAh / g, while graphite is only 372mAh / g. Under the same volume or weight conditions, silicon-carbon negative electrodes can store more energy and improve the battery's endurance. Therefore, silicon-carbon electrodes have a profound impact on improving the performance of lithium-ion batteries and the development of the new energy industry, and are expected to further promote the efficient use of energy and sustainable development of the environment in the future. However, silicon materials face the problem of volume expansion during the charging and discharging process, which leads to poor battery cycle stability. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor cycle stability of lithium-ion batteries using silicon-carbon composite materials as negative electrodes in the prior art, thereby providing a lithium-ion battery with a silicon-carbon negative electrode.

[0005] To this end, the present invention provides the following technical solutions.

[0006] The present invention provides a lithium-ion battery with a silicon-carbon negative electrode, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm;

[0007] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode sheet, wherein the negative electrode active material layer comprises a silicon-carbon composite material;

[0008] The silicon-carbon composite material has a Raman wavelength of 470-480 cm -1 There are characteristic peaks at 1, 507-517cm -1 There are characteristic peaks at 2, 1330-1350cm -1 There are characteristic peaks at 3, 1590-1610cm -1 There is a characteristic peak 4 at

[0009] The Raman spectrum characteristics of the silicon-carbon composite material satisfy: (D1+D3) / (D2+D4)=K, 0.5≤K≤3; D1, D2, D3, D4 correspond to the intensities of characteristic peak 1, characteristic peak 2, characteristic peak 3, and characteristic peak 4, respectively;

[0010] The electrolyte includes an additive A1, wherein A1 is a compound having a structure of formula I:

[0011]

[0012] In Formula I, R1, R2, R3, and R4 are each independently selected from acyloxy, cyano, isocyano, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C1-C5 alkenyl, substituted or unsubstituted aryl, and substituted or unsubstituted C1-C5 alkoxy; when substituted, the substituents are each independently selected from fluorine and C1-C4 alkyl; or R1 and R2 are linked together with the carbon atom connecting them to form a C4-C 20 or R1 and R2 are connected to form an oxygen-containing heterocycle with the oxygen atom connecting them;

[0013] Ring A is selected from substituted or unsubstituted C5-C 10 Cycloalkanes, substituted or unsubstituted C5-C 10 Cyclic olefins;

[0014] Y - Selected from DFOB - TFSI - 、FSI - 、BOB - 、BF4 - or PF2O2 - .

[0015] In a possible implementation manner, the mass content of the additive A1 in the electrolyte is M%, where M is 0.2-5.

[0016] In a possible implementation manner, 0.1≤M / K≤5 is satisfied, and / or M is 0.2-3.

[0017] In a possible embodiment, the additive A1 At least one selected from the following structures:

[0018]

[0019] In a possible implementation, the electrolyte further includes at least one of additive A2 and additive A3;

[0020] Additive A2 includes a compound having the structure of Formula II:

[0021]

[0022] Additive A3 includes a compound having the structure of Formula III:

[0023]

[0024] In a possible implementation manner, the total mass content of the additive A2 and the additive A3 in the electrolyte is 0.2% to 4%.

[0025] In one possible embodiment, the additive A2 is selected from at least one of the following compounds:

[0026]

[0027] In one possible embodiment, the additive A3 includes a compound having one of the following structures:

[0028]

[0029] In a possible implementation, the electrolyte further comprises propyl propionate PP and ethyl butyrate EB, the sum of the mass percentages of PP and EB in the electrolyte is G%, and G is 5 to 40;

[0030] Preferably, 15≤G / M≤80.

[0031] In a possible implementation manner, the content of alcohol in the electrolyte is Z%≤0.6%;

[0032] The alcohol substance refers to a substance containing -OH in the electrolyte. When the additive A3 is contained, the alcohol substance includes the additive A3.

[0033] In a possible implementation, the electrolyte satisfies 4.5≤pH≤7.

[0034] In a possible implementation, the electrolyte further includes a phosphorus-containing additive, N% is the mass content of the phosphorus-containing additive in the electrolyte, and N is 0.1 to 5;

[0035] In a possible implementation, 2≤N / M≤10 is satisfied;

[0036] Preferably, the phosphorus-containing additive includes at least one of hexafluorocyclotriphosphazene, tris(2,2,2-trifluoroethyl) phosphate, tris(2-cyanoethyl)phosphite, triallyl phosphate, and triphenyl phosphate;

[0037] In a possible implementation, the silicon-carbon composite material includes a porous carbon substrate, silicon dispersed in pores of the porous carbon, and a carbon coating layer located on the surface of the porous carbon substrate.

[0038] The technical solution of the present invention has the following advantages:

[0039] 1. The lithium-ion battery with silicon-carbon negative electrode of the present invention comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side of the negative electrode sheet, and the negative electrode active material layer comprises a silicon-carbon composite material; the silicon-carbon composite material has a Raman test at 470-480cm -1 There are characteristic peaks at 1, 507-517cm -1 There are characteristic peaks at 2, 1330-1350cm -1 There are characteristic peaks at 3, 1590-1610cm -1 There is a characteristic peak 4 at the position; the Raman spectrum characteristics of the silicon-carbon composite material satisfy: (D1+D3) / (D2+D4)=K, 0.5≤K≤3; D1, D2, D3, and D4 correspond to the intensities of characteristic peak 1, characteristic peak 2, characteristic peak 3, and characteristic peak 4, respectively; the electrolyte includes an additive A1, and A1 is a compound having a structure of formula I: In Formula I, R1, R2, R3, and R4 are each independently selected from acyloxy, cyano, isocyano, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C1-C5 alkenyl, substituted or unsubstituted aryl, and substituted or unsubstituted C1-C5 alkoxy; when substituted, the substituents are each independently selected from fluorine and C1-C4 alkyl; or R1 and R2 are linked together with the carbon atom connecting them to form a C4-C 20 or R1 and R2 are connected to form an oxygen-containing heterocycle with the oxygen atom connecting them; Ring A is selected from substituted or unsubstituted C5-C 10 Cycloalkanes, substituted or unsubstituted C5-C 10 Cyclic olefin; Y - Selected from DFOB - (difluorooxalatoborate), TFSI - (Bis(trifluoromethanesulfonyl)imide), FSI - (Bis(fluorosulfonyl)imide), BOB - (bis(oxalatoboric acid)borate), BF4 - (fluoroborate) or PF2O2 - (difluorophosphate).

[0040] 0.5≤K≤3, the order and defect amount of the surface of the silicon-carbon composite material are both within a suitable range, which is more conducive to the additive A1 to form a SEI film on the surface of the silicon-carbon composite material, avoiding breakage and shedding during the battery cycle, and also avoiding excessive decomposition of electrolyte components on the material surface to form an excessively thick SEI film, which can improve the battery cycle performance while reducing the battery impedance. The present invention introduces diaziridinium and nitrogen-containing heterocyclic additive A1 into the electrolyte. The ketone group / nitrogen of the nitrogen-containing heterocyclic compound can coordinate with more lithium ions, and the heterocyclic ring has a large steric hindrance, which is conducive to the compound to transport solvated lithium ions to participate in the SEI film reaction and prevent other active solvents from having side reactions at the interface. The order and defects of specific silicon-carbon are appropriate, and there are appropriate active functional groups on the surface, which can interact with additive A1 and will not excessively catalyze the decomposition of the electrolyte. The diaziridinium compound can adsorb on the active functional groups such as hydroxyl and carboxyl groups on the surface of the silicon-carbon material, and after the reaction, a SEI film component of a nitrogen-containing polymer is formed, which is conducive to accelerating the ion embedding reaction (the lone pair of electrons of nitrogen and Li + The nitrogen-containing components can improve the stability of the SEI film through hydrogen bonding interactions (NH…N, CH…N), and the expansion / contraction process of the silicon material realizes the elastic work of the SEI film.

[0041] Additive A1 interacts with specific silicon-carbon materials, which is beneficial to promoting the formation of SEI film, improving the ion conductivity, stability and elasticity of the SEI film, thereby improving the cycle stability and safety of the silicon-carbon battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 This is the Raman spectrum of the silicon-carbon composite material in Example 1. DETAILED DESCRIPTION

[0044] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0045] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0046] The present invention provides a lithium-ion battery with a silicon-carbon negative electrode, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm;

[0047] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode sheet, wherein the negative electrode active material layer comprises a silicon-carbon composite material;

[0048] The silicon-carbon composite material has a Raman wavelength of 470-480 cm -1 There are characteristic peaks at 1, 507-517cm -1 There are characteristic peaks at 2, 1330-1350cm -1 There are characteristic peaks at 3, 1590-1610cm -1 There is a characteristic peak 4 at the position; the Raman spectrum characteristics of the silicon-carbon composite material satisfy: (D1+D3) / (D2+D4)=K, 0.5≤K≤3;

[0049] The electrolyte includes an additive A1, wherein A1 is a compound having a structure of formula I:

[0050]

[0051] In Formula I, R1, R2, R3, and R4 are each independently selected from acyloxy, cyano, isocyano, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C1-C5 alkenyl, substituted or unsubstituted aryl, and substituted or unsubstituted C1-C5 alkoxy; when substituted, the substituents are each independently selected from fluorine and C1-C4 alkyl; or R1 and R2 are linked together with the carbon atom connecting them to form a C4-C 20 or R1 and R2 are connected to form an oxygen-containing heterocycle with the oxygen atom connecting them;

[0052] Ring A is selected from substituted or unsubstituted C5-C 10 Cycloalkanes, substituted or unsubstituted C5-C 10 Cyclic olefins;

[0053] Y - Selected from DFOB - TFSI - 、FSI - 、BOB - 、BF4 - or PF2O2 - .

[0054] The order and defect amount of the silicon-carbon composite material surface are both within an appropriate range, which is more conducive to the additive A1 to form a SEI film on the surface of the silicon-carbon composite material to avoid breakage and shedding during battery cycling. It can also avoid excessive decomposition of electrolyte components on the material surface to form an excessively thick SEI film, which can improve the battery's cycling performance while reducing the battery impedance.

[0055] In a possible implementation manner, the mass content of the additive A1 in the electrolyte is M%, where M is 0.2-5, and can be optionally 0.2-3.

[0056] In one possible implementation, 0.1≤M / K≤5 is satisfied. The following can be achieved: 1. The ketone group / nitrogen of the nitrogen-containing heterocyclic ring can coordinate with more lithium ions, and other solvents can be prevented from having side reactions at the interface through large steric hindrance, which is beneficial for the nitrogen-containing heterocyclic compound to transport solvated lithium ions and participate in the SEI film reaction. 2. Diazolidinium imide can be adsorbed on active functional groups such as hydroxyl and carboxyl groups on the surface of silicon-carbon materials to form SEI film components of nitrogen-containing polymers, which is beneficial to accelerate ion transfer in the SEI film (the lone pair of electrons of nitrogen interacts with Li+). 3. The nitrogen-containing component can achieve elastic repair of the SEI film during the expansion / contraction process of the silicon material through hydrogen bond interactions (NH…N, CH…N). 0.1≤M / K≤5 can prevent the SEI film from being too thick, and improve the low-temperature cycle capacity retention rate, cycle stability, and charge and discharge rate performance of the battery.

[0057] In a possible embodiment, the additive A1 At least one selected from the following structures:

[0058]

[0059]

[0060] In a possible implementation, the electrolyte further includes at least one of additive A2 and additive A3;

[0061] Additive A2 includes a compound having the structure of Formula II:

[0062]

[0063] Additive A3 includes a compound having the structure of Formula III:

[0064]

[0065] On the one hand, additive A1 can consume trace water in the electrolyte, preventing lithium salt from undergoing hydrolysis in an environment with trace water, thereby generating harmful products such as hydrofluoric acid (HF) and phosphoric acid. On the other hand, additive A2 and additive A3 work together to exert the effect of additive A1, which can solve the problem that the larger molecular structure of additive A1 increases electrolyte viscosity and deteriorates battery impedance after addition; additive A1, additive A2 and additive A3 work together to improve the effect of forming the SEI film.

[0066] In a possible implementation manner, the total mass content of the additive A2 and the additive A3 in the electrolyte is 0.2% to 4%.

[0067] In a possible implementation, at least one of the following conditions is met:

[0068] (1) Additive A2 is at least one selected from the following compounds:

[0069]

[0070] (2) Additive A3 includes a compound having one of the following structures:

[0071]

[0072] In a possible implementation, the electrolyte further includes PP (propyl propionate) and EB (ethyl butyrate), the sum of the mass percentages of PP and EB in the electrolyte is G%, and G is 5 to 40. Compared with other solvents EP (ethyl propionate), EA (ethyl acetate), and MP (methyl propionate), PP and EB have higher voltage stability and a wider temperature range, and G is 5 to 40, which can control the viscosity of the electrolyte within a reasonable range, avoid adverse effects on the battery conductivity and charge and discharge efficiency, and is beneficial to the thermal stability of the electrolyte, ensuring the high temperature storage performance of the battery.

[0073] Preferably, 15≤G / M≤80. Within this range, the solvating ability of esters such as PP and EB is weaker than that of additive A1, and PP and EB solvents can be excluded from the inner layer of the solvated lithium ion structure formed by additive A1. Additive A1 participates in the formation of the SEI film, preventing EB and PP solvents from participating in the interface side reaction to generate an unstable SEI film and release hydrogen, alkanes, and alkenes, thereby improving the overcharge performance of the battery, and the battery remains safe during long-term charging.

[0074] Preferably, the content of alcohol in the electrolyte is Z%≤0.6%; since the electrolyte cyclic carbonate (such as EC, PC), carboxylate (such as EP, PP, EB), carbonate (such as EMC, DMC, DEC) solvents decompose to produce alcohol during the battery cycle process, the additive A3 is also an alcohol. By controlling the content of alcohol in the electrolyte Z%≤0.6%, it is possible to prevent the protons of the alcohol from consuming active lithium ions in the electrolyte, catalyzing the oxidative decomposition of electrolyte components, and producing side reactions with SEI membrane components, thereby reducing the battery cycle performance. At the same time, the additives A1 and A2 can react with hydroxyl groups (lone pair electrons and hydrogen), and the content of alcohol in the electrolyte can also be reduced.

[0075] Preferably, the electrolyte satisfies 4.5≤pH≤7. The lithium salt of the electrolyte is prone to hydrolysis reaction in an environment where trace water exists, generating hydrofluoric acid (HF) and phosphoric acid substances, which damage the comprehensive electrochemical performance of the battery. Additive A1 can react with the proton hydrogen of the acidic substance, satisfying: 4.5≤pH≤7. Additive A1 reacts with water and acidic substances in the electrolyte to form precipitates or harmless products, which are converted into non-acidic or low-toxic products to reduce the acidity of the electrolyte, which is beneficial to improving the performance of the battery and extending its service life.

[0076] In a possible implementation, the electrolyte further includes a phosphorus-containing additive, N% is the mass content of the phosphorus-containing additive in the electrolyte, N is 0.1 to 5, and can be optionally 1 to 5;

[0077] In one possible implementation, 2≤N / M≤10 is satisfied. The phosphorus-containing compound and the additive A1 work synergistically to absorb the free radicals required for combustion when the battery is punctured or other accidents occur, thereby reducing safety risks. At the same time, the SEI film formed by A1 can inhibit the phosphorus-containing compound from reacting with the interface to generate byproducts such as phosphoric acid that corrode the battery, thereby improving the battery cycle stability.

[0078] Preferably, the phosphorus-containing additive includes at least one of hexafluorocyclotriphosphazene, tris(2,2,2-trifluoroethyl) phosphate, tris(2-cyanoethyl)phosphite, triallyl phosphate, and triphenyl phosphate.

[0079] In a possible implementation, in the silicon-carbon composite material, the mass content of silicon is in the range of 35%-70%.

[0080] In a possible implementation, the negative electrode active material layer further includes a carbon-based active material. Optionally, the carbon-based active material includes one or more of graphite, hard carbon, soft carbon, and activated carbon.

[0081] In a possible embodiment, the negative electrode active material layer further includes a binder. Optionally, the binder includes one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), sodium alginate (SA), and polyacrylic acid (PAA).

[0082] In a possible implementation, the negative electrode active material layer further includes a conductive agent. Optionally, the conductive agent includes one or more of carbon black, conductive graphite, carbon fiber (VGCF), carbon nanotube (CNT), and graphene.

[0083] In a possible implementation, the mass content of the silicon-carbon composite material in the negative electrode active material layer is 3%-25%.

[0084] In a possible embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material, a positive electrode binder, and a conductive agent. The positive electrode active material may include at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, and lithium-rich manganese-based materials. The positive electrode binder may include at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, and polyethylene oxide. The positive electrode conductive agent includes at least one of conductive carbon black, acetylene black, ketjen black, conductive graphite, and conductive carbon fiber.

[0085] In a possible embodiment, the electrolyte may further include an additive B. The additive may include at least one of fluorophosphate, fluoroethylene carbonate, ethylene glycol bis(propionitrile) ether, adiponitrile, succinonitrile, 1,3,6-hexanetrinitrile, glutaronitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,3,4,5,6-(2-cyanoethoxy)hexane, 1,3-propanesultone, propylene-1,3 sulfonate and vinyl sulfite. Preferably, the mass content of the additive B in the electrolyte is 3%-12%.

[0086] In a possible implementation, the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium tetrafluoroborate. Preferably, the content of the lithium salt in the electrolyte is 10-18 wt %.

[0087] In a possible embodiment, the diaphragm is a 5-10 μm thick common substrate such as polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, etc., coated with a ceramic layer and / or polyvinylidene fluoride layer with a thickness of 1-3 μm.

[0088] Example 1

[0089] This embodiment provides a method for preparing a silicon-carbon negative electrode lithium ion battery, comprising the following steps:

[0090] (1) Preparation of positive electrode

[0091] Lithium cobalt oxide, binder polyvinylidene fluoride (PVDF 500), and conductive carbon material (Super P) were mixed in N-methylpyrrolidone (NMP) solvent at a weight ratio of 95:2.5:2.5, and stirred continuously in a stirrer to form a uniform positive electrode slurry. Subsequently, the positive electrode slurry was coated on an aluminum foil with a thickness of 10 μm, sent to a 120°C vacuum oven for drying for 6 hours, and then rolled and cut to obtain the required positive electrode sheet.

[0092] (2) Negative electrode preparation

[0093] Graphite, silicon-carbon composite material, conductive agent carbon black (Super P), binder sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) were mixed in a water solvent at a weight ratio of 80:16:2:0.5:1.5, and continuously stirred into a uniform, flowing negative electrode slurry under the action of a stirrer. Subsequently, the slurry was coated on the surface of a 10μm thick current collector copper foil, sent to a 120℃ vacuum oven for drying for 6h, and then rolled and cut to obtain the desired negative electrode sheet.

[0094] Figure 1 The Raman spectrum of the silicon-carbon composite material of this embodiment is 470-480cm -1 There are characteristic peaks at 1, 507-517cm -1 There are characteristic peaks at 2, 1330-1350cm -1 There are characteristic peaks at 3, 1590-1610cm -1 There is a characteristic peak 4. Silicon-carbon composite material K = (D1 + D3) / (D2 + D4) = 1.25, D1, D2, D3, D4 correspond to the intensity of characteristic peak 1, characteristic peak 2, characteristic peak 3, characteristic peak 4 respectively.

[0095] (3) Preparation of electrolyte

[0096] In a glove box filled with argon (water content <1ppm, oxygen content <1ppm), ethylene carbonate (EC) and propylene carbonate (PC) are mixed in a mass ratio of 1:2 to form a uniform solvent, and LiPF6 and PP, EB, additive A1, additive A2, additive A3, additive B (fluoroethylene carbonate, 1,3-propane sultone, 1,3,6-hexane trinitrile) are slowly added to the mixed solution, and after stirring evenly, the desired lithium ion battery electrolyte is obtained, in which the content of LiPF6 in the electrolyte is 14.3wt%, the content of PP+EB G is 32wt% (including PP content 20wt%, EB content 12wt%), the content of additive A1 is 0.5wt%, the content of additive A2 is 0.2wt%, the content of additive A3 is 0.2wt%, the content of fluoroethylene carbonate is 5wt%, the content of 1,3-propane sultone is 3wt%, the content of 1,3,6-hexane trinitrile is 3wt%, and the balance is EC and PC solvents.

[0097] Additive A1 cation is Anion Y - DFOB - (Additive A1 is from Shanghai MacLean Biochemical Technology Co., Ltd.), Additive A2 is Additive A3 cation is The anion is DFOB - .

[0098] (4) Preparation of diaphragm

[0099] After coating a 1 μm boehmite layer on one side of a 7 μm polyethylene substrate, a 2 μm polyvinylidene fluoride adhesive layer was coated on both sides.

[0100] (5) Preparation of lithium-ion batteries

[0101] After the prepared positive electrode sheet, separator and negative electrode sheet are wound into a bare cell, they are fixed with adhesive tape and then placed in an aluminum-plastic film package. The prepared electrolyte is injected into the dried bare cell. After vacuum packaging, room temperature standing, high-temperature formation and other processes, the desired silicon-carbon negative electrode lithium-ion battery is obtained.

[0102] Example 2

[0103] This embodiment is basically the same as embodiment 1, except that the additive A1 cation is

[0104]

[0105] Example 3

[0106] This embodiment is basically the same as embodiment 1, except that the additive A1 cation is

[0107] Example 4

[0108] This embodiment is basically the same as embodiment 1, except that the additive A1 cation is

[0109]

[0110] Example 5

[0111] This embodiment is basically the same as embodiment 1, except that the additive A1 cation is

[0112] Example 6

[0113] This embodiment is basically the same as embodiment 1, except that the additive A1 cation is

[0114]

[0115] Example 7

[0116] This embodiment is basically the same as embodiment 1, except that the additive A1 cation is

[0117]

[0118] Example 8

[0119] This embodiment is basically the same as embodiment 1, except that the additive A1 cation is

[0120] Example 9

[0121] This embodiment is basically the same as the embodiment 1, except that the content of the additive A1 in the electrolyte prepared in step 3 is 0.2 wt %.

[0122] Example 10

[0123] This embodiment is basically the same as the embodiment 1, except that the content of the additive A1 in the electrolyte prepared in step 3 is 3 wt %.

[0124] Embodiment 11

[0125] This embodiment is basically the same as the embodiment 1, except that the content of the additive A1 in the electrolyte prepared in step 3 is 5 wt %.

[0126] Example 12

[0127] This embodiment is basically the same as Embodiment 1, except that the additive A2 is not added to the electrolyte prepared in step 3.

[0128] That is, the desired lithium-ion battery electrolyte is obtained, in which the content of LiPF6 is 14.3wt%, the content of PP+EB G is 32wt% (including 20wt% PP and 12wt% EB), the content of additive A1 is 0.5wt%, the content of additive A3 is 0.2wt%, the content of fluoroethylene carbonate is 5wt%, the content of 1,3-propane sultone is 3wt%, the content of 1,3,6-hexane trinitrile is 3wt%, and the balance is EC and PC solvents.

[0129] Embodiment 13

[0130] This embodiment is basically the same as Embodiment 1, except that the additive A3 is not added to the electrolyte prepared in step 3.

[0131] That is, the desired lithium-ion battery electrolyte is obtained, in which the content of LiPF6 is 14.3wt%, the content of PP+EB G is 32wt% (including 20wt% PP and 12wt% EB), the content of additive A1 is 0.5wt%, the content of additive A2 is 0.2wt%, the content of fluoroethylene carbonate is 5wt%, the content of 1,3-propane sultone is 3wt%, the content of 1,3,6-hexane trinitrile is 3wt%, and the balance is EC and PC solvents.

[0132] Embodiment 14

[0133] This embodiment is basically the same as Embodiment 1, except that additive A2 and additive A3 are not added to the electrolyte prepared in step 3.

[0134] That is, the desired lithium-ion battery electrolyte is obtained, in which the content of LiPF6 is 14.3wt%, the content of PP+EB G is 32wt% (including 20wt% PP and 12wt% EB), the content of additive A1 is 0.5wt%, the content of fluoroethylene carbonate is 5wt%, the content of 1,3-propane sultone is 3wt%, the content of 1,3,6-hexane trinitrile is 3wt%, and the balance is EC and PC solvents.

[0135] Embodiment 15

[0136] This embodiment is basically the same as Embodiment 1, except that, in the electrolyte prepared in step 3, the content of LiPF6 is 14.3wt%, the content of PP+EB G is 32wt% (including 20wt% PP and 12wt% EB), the content of additive A1 is 0.5wt%, the content of additive A2 is 0.2wt%, the content of additive A3 is 0.8wt%, the content of fluoroethylene carbonate is 5wt%, the content of 1,3-propane sultone is 3wt%, the content of 1,3,6-hexane trinitrile is 3wt%, and the balance is EC and PC solvents.

[0137] Comparative Example 1

[0138] This comparative example is substantially the same as Example 1, except that the additive A1 is not added.

[0139] Comparative Example 2

[0140] This comparative example is substantially the same as Example 1, except that the silicon-carbon composite material used in this comparative example has K=3.2.

[0141] The batteries prepared in the embodiments and comparative examples were tested respectively:

[0142] 1. The test method for the content Z% of alcohol substances in the battery electrolyte is: extract the electrolyte of the battery and use a gas chromatograph (GC-MS) to test the content Z% of alcohol substances in the electrolyte.

[0143] The test results are shown in Table 1.

[0144] Table 1

[0145]

[0146]

[0147] M% is the mass content of the additive A1 based on the total mass of the electrolyte. G% is the sum of the mass percentages of PP and EB based on the total mass of the electrolyte.

[0148] The electrical properties of the batteries prepared in the examples and comparative examples were tested respectively:

[0149] (1) 25℃ Cyclic Stability Test

[0150] The batteries obtained in the above embodiments and comparative examples were placed in an ambient temperature of (25±2)°C, charged to 4.5V at a constant current density of 2C, and discharged to 3.0V at a constant current density of 0.5C. The discharge capacity was recorded as the initial capacity Q0, and the discharge capacity was Q1 when the cycle reached 300 cycles, and the capacity retention rate (Q1 / Q0) was obtained.

[0151] (2) Low temperature discharge experiment

[0152] The batteries obtained in the above embodiments and comparative examples were placed in an ambient temperature of (25±2)°C, charged to 4.5V at a constant current density of 1.3C, discharged to 3.0V at a constant current density of 0.5C, and the discharge capacity was recorded as the initial capacity Q2. The batteries were then transferred to a low temperature box (maintained for 30 min), and the capacity Q3 at 0°C, Q4 at -10°C, and Q5 at -20°C were measured to obtain the capacity retention rates (Q3 / Q2, Q4 / Q2, Q5 / Q2).

[0153] (4) Acupuncture test

[0154] The batteries obtained in the above embodiments and comparative examples are pierced with a high temperature resistant steel needle with a diameter of ф8mm at a speed of (25±5)mm / s from a direction perpendicular to the battery plate. The puncture position is preferably close to the geometric center of the punctured surface (the steel needle stays in the battery), and the battery status is recorded. If the battery does not catch fire or explode, it means it has passed.

[0155] (5) Overcharge performance test

[0156] The batteries obtained in the above examples and comparative examples were placed in an ambient temperature of (25±2)°C and charged at 0.5C for 3 hours, or stopped when the voltage reached 10 V. The battery status was recorded, and the battery passed when it did not catch fire or explode.

[0157] The test results are shown in Table 2, Table 4 and Table 6.

[0158] Table 2

[0159]

[0160] In the puncture test in Table 2, P is passed and T is tested, for example, 10P / 10T means 10 tests and 10 passes. By comparing Examples 1 to 15 with Comparative Examples 1 to 2 in Table 2, it can be seen that the cycle stability, capacity retention rate and safety performance of the battery of the present application are significantly improved.

[0161] By comparing Examples 1 to 10 with Example 11, it can be seen that when M is in the range of 0.2 to 3, the cycle performance and capacity retention rate of the battery can be further improved.

[0162] From the comparison of Example 1, Example 12, Example 13 and Example 14, it can be seen that the electrolyte containing additives A2 and A3 can further improve the cycle performance and capacity retention rate of the battery.

[0163] From the comparison between Example 1 and Example 15, it can be seen that satisfying Z%≤0.6% can further improve the battery cycle stability, capacity retention rate and safety performance of the battery.

[0164] Example 16

[0165] This embodiment is basically the same as embodiment 1, except that the electrolyte prepared in step (3) further includes 2 wt % of hexafluorocyclotriphosphazene.

[0166] Embodiment 17

[0167] This embodiment is basically the same as embodiment 1, except that the electrolyte prepared in step (3) further includes 1 wt % of hexafluorocyclotriphosphazene.

[0168] Embodiment 18

[0169] This embodiment is basically the same as embodiment 1, except that the electrolyte prepared in step (3) further includes 5 wt % of hexafluorocyclotriphosphazene.

[0170] Table 3

[0171] N M N / M Example 16 2 0.5 4.00 Embodiment 17 1 0.5 2.00 Embodiment 18 5 0.5 10.00

[0172] N% is the mass content of the phosphorus-containing additive in the electrolyte.

[0173] Table 4

[0174]

[0175] It can be seen from Example 1 and Example 16 to Example 18 that the addition of phosphorus-containing additives can improve the cycle performance, puncture and overcharge performance of the battery. And it can be seen from Example 16 to Example 18 that as the amount of phosphorus-containing additive added increases, the cycle performance gradually improves.

[0176] Embodiment 19

[0177] This embodiment is basically the same as Embodiment 16, except that M=2.9, K=0.53, and M / K=5.47.

[0178] Embodiment 20

[0179] This embodiment is basically the same as Embodiment 16, except that in the electrolyte, the content of PP+EB is 5wt%, and G / M=10.

[0180] Embodiment 21

[0181] This embodiment is basically the same as embodiment 16, except that in the electrolyte, the PP+EB content G is 10 wt%.

[0182] Embodiment 22

[0183] This embodiment is basically the same as Embodiment 16, except that in the electrolyte, the PP+EB content G is 40 wt%.

[0184] Table 5

[0185] Serial number K M M / K G G / M Embodiment 19 0.53 2.9 5.47 32 11.03 Embodiment 20 1.25 0.5 0.40 5 10.00 Embodiment 21 1.25 0.5 0.40 10 20.00 Embodiment 22 1.25 0.5 0.40 40 80.00

[0186] Table 6

[0187]

[0188] By comparing Example 16 with Example 19, it can be seen that satisfying 0.1≤M / K≤5, N / M is in the range of 2 to 10, and G / M is in the range of 15 to 80 can further improve the battery cycle stability, capacity retention rate and safety performance of the battery.

[0189] By comparing Example 16 with Example 20, it can be seen that when G / M is in the range of 15 to 80, the pass rate of the battery's puncture test and overcharge test can be further improved, thereby improving the battery's safety performance.

[0190] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A lithium-ion battery with a silicon-carbon negative electrode, characterized in that: Including positive electrode sheet, negative electrode sheet, electrolyte and separator; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode sheet, wherein the negative electrode active material layer comprises a silicon-carbon composite material; The silicon-carbon composite material has a Raman wavelength of 470-480 cm -1 There are characteristic peaks at 1, 507-517cm -1 There are characteristic peaks at 2, 1330-1350cm -1 There are characteristic peaks at 3, 1590-1610cm -1 There is a characteristic peak 4 at The Raman spectrum characteristics of the silicon-carbon composite material satisfy: (D1+D3) / (D2+D4)=K, 0.5≤K≤3; D1, D2, D3, D4 correspond to the intensities of characteristic peak 1, characteristic peak 2, characteristic peak 3, and characteristic peak 4, respectively; The electrolyte includes an additive A1, wherein A1 is a compound having a structure of formula I: In Formula I, R1, R2, R3, and R4 are each independently selected from acyloxy, cyano, isocyano, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C1-C5 alkenyl, substituted or unsubstituted aryl, and substituted or unsubstituted C1-C5 alkoxy; when substituted, the substituents are each independently selected from fluorine and C1-C4 alkyl; or R1 and R2 are linked together with the carbon atom connecting them to form a C4-C 20 or R1 and R2 are connected to form an oxygen-containing heterocyclic ring with the oxygen atom connecting them; Ring A is selected from substituted or unsubstituted C5-C 10 Cycloalkanes, substituted or unsubstituted C5-C 10 Cyclic olefins; Y - Selected from DFOB - TFSI - 、FSI - 、BOB - 、BF4 - or PF2O2 - .

2. The lithium-ion battery with silicon-carbon negative electrode according to claim 1, characterized in that: The mass content of the additive A1 in the electrolyte is M%, where M is 0.2-5.

3. The lithium-ion battery with silicon-carbon negative electrode according to claim 2, characterized in that: Satisfies 0.1≤M / K≤5, and / or M is 0.2-3.

4. The lithium-ion battery with silicon-carbon negative electrode according to claim 1, characterized in that: The additive A1 At least one of the following structures:

5. The lithium-ion battery with silicon-carbon negative electrode according to claim 1, characterized in that: The electrolyte further includes at least one of additive A2 and additive A3; Additive A2 includes a compound having the structure of Formula II: Additive A3 includes a compound having the structure of Formula III:

6. The lithium-ion battery with silicon-carbon negative electrode according to claim 5, characterized in that: The total mass content of the additive A2 and the additive A3 in the electrolyte is 0.2% to 4%.

7. The lithium-ion battery with silicon-carbon negative electrode according to claim 5, characterized in that: At least one of the following conditions is met: (1) Additive A2 is at least one selected from the following compounds: (2) Additive A3 includes a compound having one of the following structures:

8. The lithium-ion battery with silicon-carbon negative electrode according to any one of claims 1 to 7, characterized in that: The electrolyte also includes propyl propionate PP and ethyl butyrate EB, the sum of the mass percentages of PP and EB in the electrolyte is G%, and G is 5-40; Preferably, 15≤G / M≤80.

9. The lithium-ion battery with silicon-carbon negative electrode according to claim 8, characterized in that: The content of alcohol in the electrolyte is Z%≤0.6%; and / or The electrolyte satisfies 4.5≤pH≤7.

10. The lithium-ion battery with silicon-carbon negative electrode according to any one of claims 1 to 7, characterized in that: At least one of the following conditions is met: (1) The electrolyte further includes a phosphorus-containing additive, N% is the mass content of the phosphorus-containing additive in the electrolyte, and N is 0.1 to 5; Preferably, 2≤N / M≤10 is satisfied; Preferably, the phosphorus-containing additive includes at least one of hexafluorocyclotriphosphazene, tris(2,2,2-trifluoroethyl) phosphate, tris(2-cyanoethyl)phosphite, triallyl phosphate, and triphenyl phosphate; (2) The silicon-carbon composite material comprises a porous carbon substrate, silicon dispersed in the pores of the porous carbon, and a carbon coating layer located on the surface of the porous carbon substrate.

Citation Information

Patent Citations

  • Electrolyte for silicon-carbon system lithium ion battery and silicon-carbon system lithium ion battery

    CN111640981A

  • Silicon-carbon composite material, negative pole piece, electrochemical device and electronic device

    CN118136791A

  • Electrolyte and lithium ion battery

    CN118712493A

  • Lithium ion battery and electric equipment

    CN118943468A

  • Cathode active material using silicone-carbon core-shell for lithium secondary battery and method for manufacturing same

    WO2013005887A1

Cited By

  • Lithium ion battery

    CN120149505A

  • A lithium-ion battery

    CN120149505B